Transcriptomic regulation of seasonal coat color change in hares - Mafalda S. Ferreira (2020)
Color molts from summer brown to winter white coats have evolved in several species to maintain camouflage year-round in environments with seasonal snow. Despite the eco-evolutionary relevance of this key phenological adaptation, its molecular regulation has only recently begun to be addressed. Here, we analyze skin transcription changes during the autumn molt of the mountain hare (Lepus timidus) and integrate the results with an established model of gene regulation across the spring molt of the closely related snowshoe hare (L. americanus). We quantified differences in gene expression among three stages of molt progression-"brown" (early molt), "intermediate," and "white" (late molt). We found 632 differentially expressed genes, with a major pulse of expression early in the molt, followed by a milder one in late molt. The functional makeup of differentially expressed genes anchored the sampled molt stages to the developmental timeline of the hair growth cycle, associating anagen to early molt and the transition to catagen to late molt. The progression of color change was characterized by differential expression of genes involved in pigmentation, circadian, and behavioral regulation. We found significant overlap between differentially expressed genes across the seasonal molts of mountain and snowshoe hares, particularly at molt onset, suggesting conservatism of gene regulation across species and seasons. However, some discrepancies suggest seasonal differences in melanocyte differentiation and the integration of nutritional cues. Our established regulatory model of seasonal coat color molt provides an important mechanistic context to study the functional architecture and evolution of this crucial seasonal adaptation.